Distribution and Biological Activities of the Flavonoid Luteolin - Lopez-Lazaro, Miguel (Mini Reviews in Medicinal Chemistry, 2009)
Epidemiological evidence suggests that flavonoids may play an important role in the decreased risk of chronic diseases associated with a diet rich in plant-derived foods. Flavonoids are also common constituents of plants used in traditional medicine to treat a wide range of diseases. The purpose of this article is to summarize the distribution and biological activities of one of the most common flavonoids: luteolin. This flavonoid and its glycosides are widely distributed in the plant kingdom; they are present in many plant families and have been identified in Bryophyta, Pteridophyta, Pinophyta and Magnoliophyta. Dietary sources of luteolin include, for instance, carrots, peppers, celery, olive oil, peppermint, thyme, rosemary and oregano. Preclinical studies have shown that this flavone possesses a variety of pharmacological activities, including antioxidant, anti-inflammatory, antimicrobial and anticancer activities. The ability of luteolin to inhibit angiogenesis, to induce apoptosis, to prevent carcinogenesis in animal models, to reduce tumor growth in vivo and to sensitize tumor cells to the cytotoxic effects of some anticancer drugs suggests that this flavonoid has cancer chemopreventive and chemotherapeutic potential. Modulation of ROS levels, inhibition of topoisomerases I and II, reduction of NFkappaB and AP-1 activity, stabilization of p53, and inhibition of PI3K, STAT3, IGF1R and HER2 are possible mechanisms involved in the biological activities of luteolin.
Keywords: antioxidant